The way home [videorecording (DVD)] - Dreesen, Lance W.; Cain, Dean; Edgeman, Lori Beth; Shroyer, Sonny, 1935-; Nowicki, Tom (Lions Gate, 2010)
Randy Simpkins is a husband and father who is torn between the demands of his job and commitment to his family. Asked by his wife Christal to watch their two-year-old son Joe, Randy is distracted by work and Joe disappears. Randy and Christal desperately search for their missing son alongside hundreds of others from their church and community. Their strained marriage must now weather the ultimate test, the potential loss of a child.